Audit Tata Kelola Teknologi Informasi dan Proses Investasi Sistem Penerimaan Peserta Didik Baru (SPPDB) Dengan Pendekatan Framework COBIT 4.1 (Studi Kasus Pada Politeknik Negeri Bandung) - Ikhsan Muharom; Darya Setia Nugraha (Indonesian Accounting Literacy Journal, 2020)
Bandung State Polytechnic is one of the educational institutions that has applied information technology in its operational activities. one of the information technologies implemented in Polban is the New Student Admissions System (SPPDB). This system is implemented to assist Polban in the process of admitting new students so that it can be carried out effectively and efficiently. However, in recent years, the Information Technology applied by the online New Student Admissions System at Polban has not been used optimally, such as errors in online-based new student admissions. One way to optimize the management of the PPDB Polban information system is by conducting an Information System Audit to identify IT Control, IT investment processes and measuring the maturity level of IT Governance using the COBIT 4.l framework. The IT Process for each COBIT domain is selected based on the relationship between IT investment and PPDB Polban management. The results of the research on IT governance of the Polban SPPDB system obtained a maturity level of 2.9 or at level 2 (Repeatable but Intuitive). The results of this audIT Process and the recommendations are expected to be a reference in the development and improvement of the Polban Online New Student admissions system in order to optimize its services.